2019
DOI: 10.1038/s41598-019-51154-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of autosomal and male DNA extracted from casework samples using Casework Direct Kit, Custom and Maxwell 16 System DNA IQ Casework Pro Kit for autosomal-STR and Y-STR profiling

Abstract: Short repetitive regions in autosomal and Y chromosomes known as short tandem repeats (STRs) are currently used for DNA profiling in crime investigations. However, DNA profiling requires a sufficient quality and quantity of DNA template, which is often not obtained from trace evidence or degraded biological samples collected at the scene of a crime. Here, we assessed autosomal and male DNA components extracted from crime scene and mock casework samples using the Casework Direct Kit, Custom and compared the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Reagents that directly lyse cells in casework (i.e., non‐reference) samples have also been developed. For example, the Casework Direct kit, Custom (Promega) contains a buffer and reducing agent to generate PCR amplification‐ready lysates from biological stains and touch samples (Graham et al, 2018; Hakim et al, 2019). In one study, the authors used a combination of microFLOQ™ Direct swabs for sample collection together with pre‐PCR amplification treatment using the Casework Direct kit, Custom to prepare lysates for direct PCR amplification (Sherier et al, 2020).…”
Section: Bypassing Dna Extraction (Direct Pcr Amplification)mentioning
confidence: 99%
“…Reagents that directly lyse cells in casework (i.e., non‐reference) samples have also been developed. For example, the Casework Direct kit, Custom (Promega) contains a buffer and reducing agent to generate PCR amplification‐ready lysates from biological stains and touch samples (Graham et al, 2018; Hakim et al, 2019). In one study, the authors used a combination of microFLOQ™ Direct swabs for sample collection together with pre‐PCR amplification treatment using the Casework Direct kit, Custom to prepare lysates for direct PCR amplification (Sherier et al, 2020).…”
Section: Bypassing Dna Extraction (Direct Pcr Amplification)mentioning
confidence: 99%
“…Recent studies testing these direct casework kits have demonstrated the successful genotyping of a wide variety of sample types, with comparable or improved results over traditional processing methods [44,45,59,77–79]. One such study performed by Sherier et al focused on the optimization of a modified direct PCR method using the Casework Direct Kit, Custom (Promega) for various dilutions of body fluid stains (blood, semen, saliva; neat‐1:100 dilution) on cloth [44].…”
Section: Resultsmentioning
confidence: 99%
“…We will use a previously developed automated method that was tested in our laboratory. To use as little material as possible, DNA will be extracted from one blood spot (approximately 50 µL) [ 17 ], after which DNA will be isolated on a solid support from the Protocol IQ Casework Pro Kit for Maxwell 16 (Promega, Madison, WI, USA) (IQ) [ 35 ]. If needed, we will also test other DNA extraction methods.…”
Section: Methodsmentioning
confidence: 99%